ANALYSIS OF INCOME LOCAL RICE FARMING IN TIDAL SWAMP LAND KUBU RAYA REGENCY - Faisal Faisal; Nurliza Nurliza; Maswadi Maswadi (Fakultas Pertanian Universitas Tanjungpura, 2018)
This study aims to determine the income of farmers from the local rice farming in tidal swamp land. Research data using primary data and secondary data with the number of respondents as many as 30 people. Data analysis used is total cost analysis, revenue analysis and farm income. The results showed that the average total cost of farmers is fixed costs and variable costs is Rp.2.488.813,56,-/Ha/MT, while the average farmer’s income is Rp.8.545.197,74,-/Ha/MT and farmer income from rice farming in tidal swamp land that is equal to Rp.6.056.384,18,-/Ha/MT. This shows that the total amount of the gain from the cultivation of rice has not been able to meet the needs of the family farmers because the rates of the income of farmers are still low.Keywords : Total Cost of Production, the reception and income of farmers